Study of Ceria Nanoparticles Synthesis and the Performance of Nano-ceria Coating for High Temperature Oxidation Resistance in Combustion Atmosphere - (:unkn) unknown (My University, 2016)
Ceria (CeO2 ) nanoparticles were synthesized by the microemulsion method with Bis(2-ethylhexyl) Sulfosuccinate Sodium Salt (AOT) as the surfactant. Stirring speed during synthesis was used to optimize the process and a precipitation process was applied to dilute the surfactant. The prepared ceria nanoparticles were characterized by x-ray diffraction (XRD) and transmission electron microscopy (TEM). As the result, non-agglomerated and time-stable ceria nanoparticles were obtained with the average particles size of 2-3 nanometers. Stainless steel 316L substrates were coated by a dipping method with the help of a slide motor which provided constant speed and uniform coating layers. Both coated and uncoated SS316L samples were oxidized in dry air and combustion atmospheres to determine the effect of the nanoparticles on oxidation performance. The oxidation temperature of dry air was 800°C -900°C and that of combustion atmosphere was 650°C -850°C. The kinetic mass gaining was recorded by a thermo-gravimetric analysis system and the samples after tests were characterized by scanning electron microscopy (SEM) and XRD. According to the TGA data, the effectiveness of ceria coating was verified in the dry air. However in the combustion atmosphere, the oxidation was complicated and the whole process could be divided into three parts: an initial slow oxidation stage, an accelerating stage and a third parabolic stage. The possible reason could be the initial protection and subsequent volatilization of Cr2O3. A hypothesis of the mechanism was proposed in this study to explain the formation of these three stages. The effect of ceria nanoparticles in combustion atmosphere was highly dependent on temperature with a benefit observed only at low temperature. Mechanisms responsible for the influence of ceria on oxidation in combustion atmosphere remained unclear.
Keywords: Ceria; Combustion Atmosphere; Oxidation Resistance; Stainless Steel